Reliable change in developmental outcomes of Brain Balance® participants stratified by baseline severity - Jackson, Rebecca; Jordan, Joshua T. (Frontiers in Psychology, 2023)
The effects of comprehensive multimodal programs on developmental outcomes have not been well-studied. Emerging evidence suggests a possible role for the Brain Balance ® (BB) program, a multimodal training program, in serving as a nonpharmacologic approach to addressing cognitive, attentional, and emotional issues in youth. In this analysis, we examined the effects of 3 months of participation in the BB program on the outcomes of children and adolescents with developmental difficulties (N = 4,041; aged 4-18 years; 69.7% male). Parent-rated scores on the Brain Balance-Multidomain Developmental Survey (BB-MDS) were used to assess six areas at baseline and post-program: 1) negative emotionality; 2) reading/writing difficulties; 3) hyperactive/disruptive behavior; 4) academic disengagement; 5) motor/coordination problems; and 6) social communication problems. To estimate change from pre-to post-program, we calculated effect size (Cohen's d) and the Reliable Change Index (RCI) for groups stratified by baseline severity. There was a very large effect size for the moderate/high severity (d = 1.63) and extreme severity (d = 2.08) groups, and a large effect size for the mild severity group (d = 0.87). The average percentage of participants who observed reliable change over all BB-MDS domains was 60.1% (RCICTT) for extreme severity, 46.6% (RCICTT) for moderate/high severity, and 21.1% (RCICTT) for baseline mild severity. In additional assessments of primitive reflexes and sensory motor activity, students demonstrated significantly diminished primitive reflexes from pre-to post-participation and significant improvements in sensory motor skills including fine motor skills, gait and aerobic ability, proprioception, rhythm and timing, and eyegaze stability. Overall, these results demonstrate improvements in primitive reflex integration and sensory motor skills, as well as statistically significant reliable change in emotionality, reading/writing, behavior, academic engagement, motor skills, and social communication in BB participants from pre-to post-program, with the probability and degree of change increasing as the participants' baseline severity increases. These results contribute to the growing literature on the need for evidence-based nonpharmacologic approaches to addressing developmental issues. Future research with well-controlled designs, longitudinal follow-up, implementation across settings, and participant groups in which diagnoses are known, will help to more fully characterize the effects of the BB program.